Promoting quality in adult education: thecontribution of peer review - Liuti, Sylvia; Marchetta, Chiara (Community Notebook. People, Education and Welfare in the Society 5.0, 2025)
Thanks to the implementation of the ONE – Opening adult education Networks to European cooperation, Erasmus+ project, many CPIAs – Public Schools for Adults in Italy – have had the opportunity to learn quality evaluation through a European Peer Review methodology, updated and adapted to latest Lifelong Learning challenges, including social cohesion and inclusiveness for the most disadvantaged. Teachers who participated between 2022 and 2024 in the training sessions to become Peers and carry out reviews remain keen to be supported in continuous improvement. They have acquired not only knowledge of the methodology but also key transversal competences to readdress evaluation in adult education, confirming the importance of promoting a continuous improvement mentality that does not equate quality evaluation with formal judgements and control. This twofold approach, based on training Peers and carrying out Peer Reviews, requires a coordination body to support competence development and manage Peer Reviews among CPIAs.